Answer:
x = 5
Step-by-step explanation:
-2 -1(coeffcient of -x) = -3
-3x +3 =-12
subtract 3 (the constant) from both sides
cancelling it on the left and leaving -3x = -15
divide each side by -3 leaving x and 5
x = 5
x^2 + 6xy + 8y2
4x^2 + 3xy + 2y^2 - 5x^2 + 2xy + 6y^2
= 4x^2 + 3xy + 2y^2 + -5x^2 + 3xy + 6y^2
Combine like terms:
= 4x^2 + 3xy + 2y^2 + -5x^2 + 3xy + 6y^2
= (4x^2 + -5x^2) + (3xy + 3xy) + (2y^2 + 6y^2)
= -x^2 + 6xy + 8y^2
Answer:
where is the picture of the graph beautiful
The answer would be three
So you express fraction.
15 x (1/3)^ 3=15/27=5/9